Visual Narratives: perceptions of 4 blind young people, in front of the body image they express in physical activity classes, in the rehabilitating Corporation of the city of Medellin. (2022)
Perceptions give space to reflect on what is done in those spaces where a subject moves. Those looks are not foreign to just a handful of people, people with diverse abilities enter that team. For this work a disability was taken, the visual one. The main objective was to identify the perceptions of 4 blind young people, between 18 and 25 years old, regarding the body image that is expressed in the physical activity class. The methodology used has a qualitative and biographical-narrative approach, based on a historical-hermeneutical paradigm. In turn, the observation sheet, the narrative interview and the photobiography are used as collection instruments. A main result is that in the classes the image of the body is not only transformed by the motor movement, it is conditioned by the emotions, perceptions and methodology that is worked on. In the same way, a main conclusion is that the blind young person makes a mental construction about his body image, based on the conception he has of normal, once he makes it, he articulates two aspects: One general, evident by what he feels, he thinks and perceives of himself; and one specific, which is the help that the other gives him with specific aspects of the image that he creates. This mental image of the body is marked by events, emotions and sensations that make the young blind person act, or express himself, in a certain way in physical activity classes.